Quantitative Analysis of Anti-CEA Antibody Accumulation in Human Colorectal Carcinomas - Bares, R.; Fass, J.; Hauptmann, S.; Braun, J.; Grehl, O.; Reinartz, Ruth; Buell, U.; Schumpelick, Y.; Mittermayer, C. (Nuklearmedizin - NuclearMedicine, 1993)
In order to obtain quantitative data on intratumoral antibody accumulation we analyzed resected colorectal adenocarcinomas of 25 patients who had undergone immunoscintigraphy 4-14 days earlier. All had been injected with 0.5-1.0 mg intact anti-CEA antibody (BW 431/26) labelled with 70-80 MBq 131I. Correlation of tissue radioactivity concentrations with tumor characteristics revealed significantly higher values in necrotic compared to viable as well as in CEA-positive compared to CEA-negative viable tumor tissue indicating action of both specific and unspecific uptake mechanisms. In contrast, diagnostic results of immunoscintigraphy were influenced by tumor size only. 11 of 12 falsenegative findings were obtained in tumors <4 cm in diameter. Since ex- vivo scintigraphy of resected specimens correctly visualized all but one of these lesions, it is concluded that technical limitations of scintigraphy are the main cause of negative results of radioimmunoimaging with 131 I-labelled antibodies.Zur Gewinnung quantitativer Daten über die intratumorale Anreicherung radioaktiv markierter Antikörper wurden Operationspräparate kolorektaler Karzinome von 25 Patienten untersucht, bei denen 4-14 Tage zuvor eine Immunszintigraphie mit 0,5-1,0 mg eines intakten Anti-CEA-Antikörpers (BW 431/26), markiert mit 70-80 MBq 131J, durchgeführt worden war. Ein Vergleich der Radioaktivitätskonzentrationen im Gewebe mit histologischen Befunden ergab signifikant höhere Werte in Nekrosen verglichen mit vitalen Tumoranteilen sowie in CEA-positiven verglichen mit CEA-negativen vitalen Tumorgeweben. Dies spricht für ein gleichzeitiges Vorkommen spezifischer (CEA-abhängiger) und unspezifischer (CEA-unabhängiger) Anreicherungsmechanismen. Die szintigraphischen Resultate hingen entscheidend von der Tumorgröße ab: 11 von 12 falsch-negativen Befunden wurden bei Tumoren eines Durchmessers <4 cm erhoben. Da diese mit Ausnahme eines Herdes durch Ex-vivo-Szintigrannme des Operationspräparats korrekt lokalisiert werden konnten, dürften meßtechnische Limitationen die Hauptursache negativer Befunde der ln-vivo-lmmunszintigraphie mit 131J-markierten Antikörpern sein.
Keywords: Carcinoembryonic antigen; colorectal carcinoma; immunoscintigraphy; tumor necroses